Dynamic Flow Rate Control for Vanadium Redox Flow Batteries. (May 2017) - Fu, Jiahui; Wang, Tao; Wang, Xinhao; Sun, Jie; Zheng, Menglian
Abstract: The vanadium redox flow battery (VRB) is one of the most promising technologies for large-scale energy storage. The control of the electrolyte flow rate during its operation has significant impacts on the overall efficiency of the storage system. Although flow-rate optimization under constant current conditions has been addressed in previous studies, few have dealt with varying (dis-)charge power conditions that are common in practice. In this study, an electrochemical model of the VRB has been developed, considering concentration overpotential and the required pump power consumption. The influence of the electrolyte flow rate on the stack efficiency is investigated, and an optimization framework is proposed for determining the optimal flow rate under varying (dis-)charge power conditions. The simulation results demonstrate that the proposed framework could increase the stack efficiency by 3% and limit the electrolyte temperature increment not exceeding 1.4 K.